2022
DOI: 10.3390/ani12131629
|View full text |Cite
|
Sign up to set email alerts
|

Locally Grown Crops and Immunocastration in Fattening Heavy Pigs: Effects on Performance and Welfare

Abstract: This study aimed to explore dietary replacement soybean meal (SBM) with local pea seeds (PS-L) and the effects of surgically castrated (CM) or immunocastration (IM) in heavy male pigs, on growth performance, feeding behaviour, and tail and ear lesions. Four treatments were arranged factorially (2 × 2), with two sexes and two dietary treatments (96 pigs in eight pens). The inclusion of PS-L was 25%, 30%, and 40% during three phases (40–80 kg, 80–110 kg, and 110–140 kg, respectively). No difference in average da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 29 publications
(37 reference statements)
2
12
0
Order By: Relevance
“…2), in addition to dietary pea inclusion, the effect of castration type in male pigs (surgical, CM vs. immunocastration, IM) was evaluated during the same fattening period. In this case, as mentioned, the growth performances were shown in an earlier manuscript [14], and herein, only the amount of fat and FA composition of loins and weight losses of dry-cured hams are shown. Not all measurements were conducted on all animals in the two experiments, Exp.…”
Section: Experimental Designsmentioning
confidence: 57%
See 3 more Smart Citations
“…2), in addition to dietary pea inclusion, the effect of castration type in male pigs (surgical, CM vs. immunocastration, IM) was evaluated during the same fattening period. In this case, as mentioned, the growth performances were shown in an earlier manuscript [14], and herein, only the amount of fat and FA composition of loins and weight losses of dry-cured hams are shown. Not all measurements were conducted on all animals in the two experiments, Exp.…”
Section: Experimental Designsmentioning
confidence: 57%
“…The CM pigs were surgically castrated during the first week of age, whereas the IM pigs were kept as entire male pigs until they reached 20 weeks of age. At this point, they were vaccinated with the first dose of the anti-GnRH vaccine, followed by another dose at 24 weeks of age, using the same procedures as described in Argemí-Armengol et al [14].…”
Section: Experimental Designsmentioning
confidence: 99%
See 2 more Smart Citations
“…Škrlep et al [ 21 ] and Čandek-Potokar et al [ 22 ] reported the same effect on sensorial hardness in dry-cured meat between surgical castrated male pigs and immunocastrated male pigs (immunocastrated female pigs were not studied). The differences in the amount of feed intake and lipogenic activity may explain the varying effects between sexes reported in another previous paper [ 23 ]. The study also found that IM pigs had a higher average daily feed intake but a lower feed conversion rate than CM pigs.…”
Section: Resultsmentioning
confidence: 99%